A novel strategy for inducing enhanced mucosal HIV-1 antibody responses in an anti-inflammatory environment. - Wegmann, F; Krashias, G; Lühn, K; Laamanen, K; Vieira, S; Jeffs, SA; Shattock, R; Sattentau, Q (2011)
Prophylactic vaccination against HIV-1 sexual transmission will probably require antibody elicitation at genital mucosal surfaces. However, HIV-1 envelope glycoprotein (Env)-based antigens are weakly immunogenic, particularly when applied mucosally. The polyanion PRO 2000 is safe for human vaginal application, and thus may represent a potential formulating agent for vaginal delivery of experimental vaccine immunogens. Based upon its biochemical properties, we hypothesized that PRO 2000 might enhance mucosal immunogenicity of HIV-1 envelope glycoprotein (Env)-based antigens, promoting local and systemic immune responses. Vaginal immunization with Env-PRO 2000 resulted in significantly increased titres of Env-specific mucosal IgA and IgG in mice and rabbits, respectively, compared to Env alone, revealing modest but significant mucosal adjuvant activity for PRO 2000. In vitro, PRO 2000 associated with Env, protecting the glycoprotein from proteolytic degradation in human vaginal lavage. Unexpectedly, PRO 2000 antagonized TLR4 activation, suppressing local production of inflammatory cytokines. Since inflammation-mediated recruitment of viral target cells is a major risk factor in HIV-1 transmission, the immune modulatory and anti-inflammatory activities of PRO 2000 combined with its intravaginal safety profile suggests promise as an HIV-1 mucosal vaccine formulating agent.